Human Resources Quality and Organizational Support with Performance of Health Operation Aid Fund Manager (KEMAS: Jurnal Kesehatan Masyarakat, 2017)
Health Operational Aid Fund (HOA) is an aid to accelerate the achievement of the health-related Millennium Development Goals 2015 through improvement of primary health care performance. This study aimed to analyze relationship between quality of human resources and organizational support with performance of HOA fund manager performance. This is an explanatory quantitative study using cross section survey approach. Total sampling technique had been used to determined 48 people as the samples. Univariate analysis showed that 91.7% respondents had good performances and as many as 8.3% respondents had poor performances. Bivariate analysis showed a significant association between facilities (0.049), incentives (0.049), consulting services (0.016) and HOA fund manager performance. Multivariate analysis demonstrated a  positive and significant correlation (0.043) between consultancy services and performance of HOA fund manager performance. For quality improvement, it is suggested to coordinate the public health office should better coordinate its programs via consultancy service in Plan Of of Action verification. in the consultancy service.